Fast and Efficient Green Procedure for the Synthesis of Benzo[5,6]chromene Derivatives and Their Sulfur Analogues in Water by Organocatalyst Potassium Phthalimide-N-oxyl - Etivand, Nasser; Khalafy, Jabbar; Dekamin, Mohammad G. (Synthesis, 2020)
A simple, clean, straightforward, and environmentally benign one-pot, three-component reaction of various arylglyoxal monohydrates, β-naphthol, and barbituric acid [pyrimidine-2,4,6(1H,3H,5H)-trione] or thiobarbituric acid in the presence of catalytic amounts potassium phthalimide-N-oxyl (PPINO), as a mild and efficient organocatalyst in aqueous media under reflux conditions is reported. This transformation produced the novel diverse-substituted 12-benzoyl-8,12-dihydro-9H-benzo[5,6]chromeno[2,3-d]pyrimidine-9,11(10H)-diones and their sulfur analogues in 82–93% yield via filtration and without utilization of any chromatography. The high yields of products, very simple operation, easy workup, availability of starting materials, green process, and high atom-economy are the main benefits of this synthetic strategy.
Keywords: potassium phthalimide-N-oxyl; arylglyoxal monohydrate; benzo[5,6]chromenes; one-pot; three-component reaction; green process